Jeden język – wiele kultur. Kilka słów o wielokulturowości i międzykulturowości na lekcjach języka polskiego (rozpoznania i refleksje) .......... 137 - Gis, Anita (Tożsamość na styku kultur: 4, 2021)
ONE LANGUAGE – MANY CULTURES… A FEW WORDS ABOUT INTERCULTURALISM IN POLISH LANGUAGE LESSONS (RECOGNITION AND REFLECTION)Polish lessons in view of challenges of intercultural education, which refers to universal values,have a great importance in the didactic and educational work of a Polish teacher. These lessonssupport exploring, understanding, and accepting different cultures and also prepare for cooperationand mutual use of the achievements of various communities. This clearly demonstrates thata Polish teacher should thoughtfully and wisely contribute to shaping the personality of a youngperson and awakening their sense of civic involvement and responsibility, which includes the processof shaping their cultural identity. For these reasons, it is interesting to learn about educationalprocess during Polish lessons, including issues such as content involved and didactic situationsstudents participate in.